Analytical Study: A Message from the Film “The Message” Integrating Selected Short Scenes from the Documentary Film “The Message” by Moustapha Al-Akkad as an Educational Tool in Micro-Teaching Processes - Adawi, Gamal (Journal of Ecohumanism, 2025)
The research aims to integrate selected short scenes from the film "The Message" by Mustafa Akkad as an educational tool in micro-teaching processes in various educational subjects such as: communication, civilization, general culture, history, geography, social education, religion, homeland and society, rights, Arabic language, and others. The study is basically based on dividing the film "The Message" by the great Syrian-American director (Mustafa Akkad) - may God have mercy on him - into ten parts; each part is a short scene cut from the film. They were shown to student and teachers (231 in number) in an Arab College of Education for teacher training, so that they could arrange them in ascending order from (1) to (10) according to their importance, the most beautiful, the best, and the strongest - in their opinion - then explaining the reasons for this arrangement, and the students’ reactions after watching the parts cut from the film. The current study also proposes another approach to how to deal with the short cinematic scenes and clips from the movie “The Message” and transform them from visual scenes into a scenario (written text) that can be integrated into “meaningful” education in the style of the micro-teaching method, taking into consideration the difficulty of the matter that it is not possible to show the entire movie “The Message” to the audience of students and the target groups, due to its long duration, which is approximately three and a half hours. 231 individuals participated in the study: 89 teachers in the complementary track and 142 fourth-year students in the regular track at an Arab college of education from all specializations: The participants in the course "Arab-Islamic Civilization" were given the task of choosing the most beautiful and best short scene they liked from the film "The Message" by Moustapha Al-Akkad to prepare model practical lessons in the style of the micro-teaching method and integrate them into various educational topics. The results of the study indicated that the teacher’s integration and use of selected scenes and short clips from a documentary film, which are short films - in the style of the micro-teaching method - stimulates students’ motivation in education, contributes to their perseverance, prevents their dropout and improves their academic achievement.